Améliorer la compétence de compréhension orale dans une classe d’EFL grâce à des stratégies métacognitives (Revista de Divulgación Shimmering Words: Research and Pedagogy E-Journal, 2022)
Learning a foreign language can be a challenge for many people and listening comprehension tends to be one of the most difficult skills for English learners. Therefore, this paper reports the findings of a qualitative action research study on the impact of metacognitive strategies on the listening comprehension skill of nine learners at a private language institute. The purpose of this study was to determine how the use of metacognitive strategies might contribute to the development of the listening skill. Some workshops were designed for the intervention, and metacognitive strategies were presented to learners. Each lesson was recorded in a journal to keep track of the students’ attitudes, progress and responses to the strategies. Moreover, learners were assessed in their performance in each workshop. They were also asked about their perceptions toward the use of strategies during the listening tasks. Additionally, a listening pre-test and post-test were implemented to compare learners’ results, which were obtained before and after the intervention. Results showed that metacognitive strategies helped learners to become aware of their own learning process. They had a positive impact on their abilities in order to understand an audio, and improved leaners’ accuracy in terms of the listening tasks implemented.